Evaluation of Anti-cancer Activities of Cranberries Juice Concentrate in Osteosarcoma Cell Lines (MG-63) - Hattiholi, Aishwarya; Tendulkar, Shivani; Kumbar, Vijay; Rao, Malleswara; Kugaji, Manohar; Muddapur, Uday; Bhat, Kishore (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/Background: Osteosarcoma is one of the prevalent cancers occurring mostly in adolescents and has a high risk of malignancy. With complications involved in the current treatment strategies, alternates including the use of phytochemicals have gained fame. Cranberries are known for their exceptional health benefits and have been explored for their effective activities in various cancers. The current study aimed at evaluating the anti-cancer properties of cranberry juice concentrate (CJC) on MG-63 cell line for human osteosarcoma, by investigating its apoptotic activity through changes in cell viability and mitochondrial membrane potential. Materials and Methods: Cranberry juice concentrate was obtained by pulverization and lyophilization. The MG-63 cells were treated with 12.5-800 μg/mL of the CJC and incubated for 24, 48, and 72 hr. The percentage cell viability and IC50 values were obtained. The mitochondrial membrane potential and nuclear changes were examined. The induction of apoptosis was studied by flow cytometer using BD cell Quest 7.5.3 software. GraphPad Prism was used for statistical analysis with significant p-value at <0.05. Results: The IC50 values obtained for CJC were 847.9, 637.4, and 440.6 μg/mL for 24, 48, and 72 hr respectively. Change in the mitochondrial membrane potential and nuclear morphology was observed following incubation with CJC. Flow cytometric analysis shows cells detected at early and late apoptoic stages after treatment with CJC. Conclusion: Our result suggests that CJC has significant effects on MG-63 osteosarcoma cells and can be considered to supplement conventional therapeutic strategies.
Keywords: Apoptosis; Cranberry; MG-63; Osteosarcoma; Phytochemicals